Effect of wearing an ice cooling jacket on repeat sprint performance in warm/humid conditions - Duffield, R.; Bishop, D.; Fitzsimons, M.; Lawrence, S. (British Journal of Sports Medicine, 2003)
Objective: To examine the effect of cooling the skin with an ice jacket before and between exercise bouts (to simulate quarter and half time breaks) on prolonged repeat sprint exercise performance in warm/humid conditions.